Doing Recovery Work Together: Clients’ and Counsellors’ Social, Discursive, and Institutional Practices - Mudry, Tanya E.; Strong, Tom; Doyle, Emily M.; Sapacz, Mackenzie (Canadian Journal of Counselling and Psychotherapy, 2020)
In this conceptual paper, we offer an alternative to traditional approaches to addictive behaviours and addictions counselling. We outline practice theory and tenets of an institutional ethnographic approach used to inquire into tacit or invisible practices of addictive behaviours, the work of recovery from them, and how counselling may (or may not) be helpful. We provide a conceptual alternative to working with clients who present for counselling with addiction concerns, using case examples as in invitation to practitioners to extend their work in new ways.